Studi Klinik Khasiat dan Keamanan Sediaan Tablet Ekstrak Dibanding Rebusan Ramuan Hiperurisemia - Agus Triyono; Widhi Astana; Danang Ardianto; Fajar Novianto (Fakultas Farmasi Universitas Pancasila, 2021)
Hyperuricemia is a metabolic disorder that is often found in the community, and requires long-termtreatment. To determine the effi cacy and safety of the hyperuricemia herbs, clinical studies have been carried out on the effi cacy and safety of tablet preparations compared to boiled of the hyperuricemia herbs. The clinical study was conducted with an open label research design, randomized clinical study and parallel design. The study involved 55 subjects who had met the inclusion and exclusion criteria. Subjects were randomized and divided into groups of tablets or boiled with intervention for 28 days. The tablet group took tablets with a dose of 3x2 tablets per day and the boiled group drank infusion with a dose of 3 times a glass per day. Blood uric acid was examined at D0, D14 and D28. SGOT, SGPT, urea, and creatinine were examined at D0 and D28. The tablet reduced uric acid (7.74 mg/dL to 6.53 mg/dL) and the boiled reduced uric acid (7.93 mg/dL to 7.09 mg/dL). The administration of tablet preparations eliminates the clinical symptoms of swollen/pain of leg, swollen/pain of hand, stiff ness, pain and other symptoms at the deff erent time than boiled administration. The administration of both preparations for 28 days in the subjects did not increase the value of SGOT, SGPT, urea and creatinine and no symptoms of serious side eff ects were found.